WAYS TO DEVELOP PATRIOTISM AND THE CHARACTER OF SPIRITUAL PERFECTION OF FUTURE MILITARY PERSONNEL - Gubaydullin Damir Maratovich; Turayev Sarvar Tulkinovich (American Journals, 2023)
The article consistently analyzes the use of analytical and pedagogical theory in the development of patriotic competencies of military personnel, the fundamental use of the spiritual heritage of Eastern thinkers in their activities. This article will explore various strategies for increasing the patriotic and spiritual maturity of future servicemen. It emphasizes the importance of education of national pride, the education of decency, the development of leadership, the diagnosis of patriots and role models, the formation of consciousness and mental potential. The implementation of these directions can cultivate military personnel with a sense of patriotism, strong moral values, effective leadership skills and a resilient spirit. These qualities are essential for their loyal and dedicated service to the nation.
Keywords: Military man, Patriot, thinker, heritage, hero, educator, education. Increasing patriotism and spiritual perfection in future servicemen: strategies for achieving success